SAT0101 Possibility of bacterial infection prophylaxis of trimethoprim-sulfamethoxazole in elderly patients with rheumatoid arthritis undergoing treatment with biologics: a single-center, retrospective, case-control study. (15th June 2017) - Kikuchi, E; Aoki, N; Yoshioka, T; Okai, T
Abstract : Background: Trimethoprim-sulfamethoxazole (TMP-SMX) is widely used for the prophylaxis of Pneumocystis jiroveci pneumonia (PCP) in immunocompromised patients, but data about the prophylactic effect of TMP-SMX against bacterial infections are insufficient. Objectives: To analyze the prophylactic effect of TMP-SMX against severe bacterial infections in elderly patients with rheumatoid arthritis undergoing treatment with biologics. Methods: Data were retrospectively collected from the medical records of patients with rheumatoid arthritis at our center. We divided the elderly patients (65 years or above) who took biologic agents into two groups. The first group (TMP-SMX+) comprised patients who previously or concurrently started TMP-SMX with biologic agents for the purpose of PCP prophylaxis and continued with it throughout the treatment with biologics. The second group (TMP-SMX-) comprised patients who were not prescribed TMP-SMX throughout the treatment with biologics. We analyzed the retention rate of each group by Kaplan-Meier curves and the Wilcoxon test. The primary end point was the 18-month retention rate of biologics without severe infection (defined as hospitalization or multiple days of intravenous antibiotic treatment in the clinic, including suspected cases). Results: The TMP-SMX+ group included 30 patients with a mean age of 76.7±7.0 years. The rate of ACPA positivity was 80.0%, MTX use was 73.3%, oral steroid use was 43.3%, and bio-naive patients was 73.3%. The number of patients treated with abatacept, certolizumab pegol, etanercept, golimumab, infliximab, and tocilizumab was 13, 1, 7, 7, 1, and 1, respectively. The cumulative retention rates at 12 and 18 months were 1.000 and 0.941, respectively. Prophylactic doses of TMP-SMX were between TMX 20mg/SMX 100mg/day and TMX 91mg/SMX 457mg/day. The TMP-SMX− group included 113 patients with a mean age of 73.6±5.6 years. The rate of ACPA positivity was 79.3%, MTX use was 70.8%, oral steroid use was 54.9%, and bio-naive patients was 80.5%. The number of patients treated with abatacept, adalimumab, certolizumab pegol, etanercept, golimumab, infliximab, and tocilizumab was 15, 15, 4, 41, 7, 18, and 13, respectively. The cumulative retention rates at 12 and 18 months were 0.812 and 0.790, respectively. There was a significant difference between the retention rates in the two groups ( p =0.038, Wilcoxon test). Five patients were enrolled in both groups because another biologic agent was used in different periods. In the TMP-SMX+ group, only one patient was hospitalized for probable bacterial pneumonia (causative bacteria not detected). In the TMP-SMX− group, nine patients were hospitalized for pneumonia, three for septic arthritis, two for urinary tract infection, and two for soft tissue infection. The causative bacteria were Escherichia coli, Klebsiella oxytoca, Enterococcus faecalis and others. Furthermore, seven patients in the TMP-SMX− group were treated for PCP, whereas no patients contracted PCP in the TMP-SMX+ group. Conclusions: Prophylactic administration of TMP-SMX may reduce the risk of bacterial infection in elderly patients with rheumatoid arthritis undergoing treatment with biologics. References: Limper AH et al. Am J Respir Crit Care Med. 2011;183(1):96–128. Katsuyama et al. Arthritis Res Ther. 2014 Feb 5;16(1):R43. doi: 10.1186/ar4472. Disclosure of Interest: None declared